Spinal CRH facilitates the micturition reflex via the CRH2 receptor in rats with normal bladder and bladder outlet obstruction - Risa Shinoki; Ryosuke Jikuya; Takuma Nirei; Takeshi Fukazawa; Hiroki Takizawa; Mari Hioki; Sachi Kawaura; Tomoyuki Tatenuma; Go Noguchi; Daiki Ueno; Yusuke Ito; Mitsuru Komeya; et al. (Scientific Reports)
Abstract Lower urinary tract symptoms (LUTS) significantly affect patient quality of life. Treatment options for bladder outlet obstruction (BOO) due to benign prostatic hyperplasia (BPH) (a common cause of LUTS) are insufficient to relieve discomfort. As the incidence of BPH is increasing, new pharmacological targets for LUTS treatment are required. Corticotropin-releasing hormone (CRH) is a neuropeptide that controls normal micturition in rodents. Herein, we investigated the role of spinal CRH in regulating micturition in sham and BOO rats, and evaluated CRH as a therapeutic target for bladder dysfunction in BOO model Sprague–Dawley rats. Histological analysis, cystometry with intrathecal administration of CRH agonists/antagonists, western blotting, and real-time PCR assessed the role of CRH and its receptors (CRHR1 and CRHR2) in micturition in sham and BOO rats. CRH administration shortened the voiding interval, while pretreatment with antagonists against CRHR2 (but not CRHR1) suppressed CRH-induced frequent voiding. Western blotting confirmed CRHR1 expression in the dorsal root ganglia (DRG) and bladder, but not the spinal cord, of rats. Real-time PCR showed higher CRHR2 mRNA expression in the spinal cord and DRG than in the bladder in both groups. Overall, spinal CRH facilitates the micturition reflex via CRHR2, and is a promising therapeutic target for LUTS.